Residual leaf area index as strategy to management of pasture: structure of Tanzania grass - Santos Lemos, Nailson Lima; Ruggieri, Ana Claudia [UNESP]; Costa e Silva, Victor; Meister, Naomi Cristina; Alari, Fernando de Oliveira; Malheiros, Euclides Braga [UNESP] (Univ Federal Rural Pernambuco, 2019)
The study aims to evaluate changes structural in Tanzania grass pasture under intermittent stocking in response to different levels of residual leaf area. The experiment was carried out from the October/2009 May/2011, testing three levels of residue leaf area (0.8 - 1.6 to 2.4). The rest period was adopted according to the criterion of 95% light interception. Forage samples were harvest at points of average height, after, taken out a subsample for the separation of the morphological components to estimate the structural characteristics and productive. In the pre-grazing, there wasn't effect of leaf area index in residual dry matter forage grass Tanzania. In the post-grazing, the dry mass of leaves increased with the treatments and the dry mass of stems was similar. The use of residual leaf area index as tool to management of pastures is effective and modifies the structure of the pasture.
Keywords: light interceptation; forage mass; leaves percentage